2013
DOI: 10.4236/jwarp.2013.59088
|View full text |Cite
|
Sign up to set email alerts
|

Boron Removal by Electrocoagulation Using Full Factorial Design

Abstract: Saline waters treatment has become increasingly important for drinking water supply in a greater part of the world. However, some serious limitations had recently been discovered during water treatment, among them the boron problem seems to have a critical meaning. According to the WHO regulations (2011), the boron concentration should be reduced to less than 2.4 mg/L for drinking water. The purpose of this study is to investigate the feasibility of electrocoagulation (EC) as a pretreatment process to remove b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Such evidence can be observed in Figure 3, in which the increase in NaNO 3 concentration increased boron removal. These results agree with the literature data [16, 17].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Such evidence can be observed in Figure 3, in which the increase in NaNO 3 concentration increased boron removal. These results agree with the literature data [16, 17].…”
Section: Resultssupporting
confidence: 94%
“…This is deposited on the surface of the electrode in a process called passivation, in which there is an increase in the resistance of the system and decrease in the efficiency of the method. Thus, despite increasing current density, a significant percentage difference in boron removal was not observed [16]. An alternative to reduce the passivation of electrodes is the addition of soluble anions with aluminum, such as chlorides and nitrates, because such species aid in the solubilization of the formed oxide.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, electrical energy consumption costs (EECC) of the electrodes at experimental conditions with high removal efficiencies are calculated according to Eq. (23) [41].…”
Section: Evaluation Of Electrical Energy Consumption Of Ec Systemmentioning
confidence: 99%
“…Previous studies have shown that the EC method is an effective tool for treating various water contaminants in textile wastewater [12,20,21,28], chemical fiber wastewater [29], algae or microorganisms [30], oily wastewater [31][32][33], restaurant wastewater [34,35], sewage water [35], arsenic [36][37][38], fluoride [39][40][41][42], boron [43,44], and nitrite [45,46]. The EC process has also been utilized in the removal of different metal ions from water, e.g.…”
Section: Introductionmentioning
confidence: 99%